Does Spirituality Influence Happiness and Academic Performance? - David, Rajasekhar (2022)
One of the key issues of the learning experience is students’ performance during the course, as this is pointed to as one of the main indicators for boosting competences’ development and skills’ improvement. This study explores the roles of spirituality, forgiveness, and gratitude on students’ academic performance, proposing a model of analysis revealing a first-order moderation effect of spirituality in the mediation effect of happiness, on the relation between gratitude and forgiveness with students’ academic performance. Two hundred twenty management students from various Indian universities voluntarily participated in the study. To avoid common method-bias issues, data concerning the study variables were obtained in two distinct moments. To test for the moderated-mediation model of analysis, we have followed the PROCESS analytical procedure. Results showed that forgiveness and gratitude were positively and significantly related to happiness and academic performance. It was also possible to see that spirituality moderates the relationship between forgiveness for self and student happiness. Finally, the moderated-mediating impact of spirituality and happiness on the relationship between gratitude and academic performance was also supported. The present study has taken the lead from positive psychology to assess the students’ character strengths related to their well-being and success. It proposes an innovative model of analysis, supported by theoretical reasoning, pointing to the existence of a moderated-mediation relation predicting students’ academic performance.